Impact of a public sensitization campaign on migraine management in France - Donnet, Anne (Springer Milan, 2009)
Migraine is a common and frequently disabling condition. Nevertheless, many migraine sufferers do not consult for migraine, are not medically followed up and self-treat the attacks. “Tour de France of migraine” consisted of free-access conferences held in six large towns in France following a wide public information campaign. This sensitization campaign aimed at providing participants with educational information on migraine disease and on current therapies. Headache sufferers were then invited to respond to two consecutive questionnaires delivered at the end of the conferences and 3 months later to assess the influence of the information delivered on their migraine management. Tour de France of migraine recruited mainly severe migraine sufferers, most of whom had already consulted and were medically followed up. However, migraine management was often suboptimal in these subjects since most of them found their acute treatment of attacks ineffective and only few of them received a prophylactic treatment. Three months after the conferences, more than half of respondents had consulted for headaches. There was a significant improvement in migraine-related disability, as reflected by a significant decrease in mean Headache Impact Test 6-item score, which might have been related to the higher proportion of subjects receiving a prophylactic treatment of migraine. The Tour de France of migraine campaign revealed the difficulty in sensitizing migraine sufferers towards the necessity of being medically followed up. Mainly patients with severe migraine attended the conferences and derived clinical benefit from the educational program. Other strategies should be developed to reach a wider population of migraine sufferers.